«By the pricking of their thumbs»: farmers’ income dynamics towards sustainable development in rural Ethiopia - Elena Urquía-Grande; Raquel Pérez-Estébanez; Elisa Isabel Cano-Montero; Julián Chamizo-González (Revista Iberoamericana de Estudios de Desarrollo)
International cooperation priorities and Sustainable Development Goals agree on the linkage between agriculture and economics in developing countries’ progress towards sustainability. In rural Ethiopia, agriculture is the major source of income and livelihood. In this study, it is aimed to analyse the association between farmers’ experience, education, gender, cultivation of crop diversity, access to various financial resources and income levels among different villages. The methodology adopted is action research, performed during various research stays in rural Ethiopia, and using both qualitative and quantitative surveys. The quantitative results were analysed through multivariate statistical analysis. Interesting results emerge; for example, farmers from rural villages that have been using wells previously donated by the non-profit organization (NPO) show various positive impacts. They attend continuous training in agriculture, nutrition, and economics; they have more crop diversification, and they use varied financial resources. All these factors, as well as socio- demographic variables, link farmers’ income levels to villages’ improvement and empowerment, creating significant challenges for institutional design of alternative policies to maximize farmers’ livelihood, sustainability and socioeconomic development in Third World countries. The article adds to the very small body of research, particularly of quantitative analysis, on factors associated with farmers’ income in Africa based on primary data.